FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MASYARAKAT TERHADAP PENCEGAHAN COVID-19 DI DESA PARANGTRITIS KECAMATAN KRETEK KABUPATEN BANTUL YOGYAKARTA - Siska Nur Aisyah Rohman; Dwi Sarwani Sri Rejeki; Sri Nurlaela (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Background: COVID-19 is highly contagious and pathogenic. Parangtritis village is a tourist village with high mobility and has fluctuating cases. Preventive behavior should be carried out by the community to reduce existing cases, because currently no specific drugs have been found to treat. The research was conducted with the aim of finding out the factors that affect the COVID-19 prevention behavior of parangtritis villagers. Method: Analytical research, cross sectional approach. The population of Parangtritis village is 5729 people. 396 samples with accidental sampling. The variables studied were gender, age, education, exposure to sources of information, knowledge and attitudes. Data collection using questionnaires through google form. Data is analyzed into univariate, bivariate, and multivariate. Result: Most of them are female (62.1%). Dominant age in the range of 15-29 years (88.1%). Secondary education level (47.7%). Covid-19 prevention resources came from social media (internet) (67.2%), with good category (71%). Good knowledge (94.4%). Good attitude (55.6%). Good behavior (72.2%). The factors that most influence COVID-19 prevention behavior are exposure to information sources (p-value= 0.000; POR= 11,622; CI= 6,755-19,994) and attitude (p-value= 0.000; POR= 2,725; CI= 1,596-4,652). Conclusion: There is sex, age, education, exposure to information sources, knowledge and attitudes towards COVID-19 prevention behavior. Exposure to sources of information and attitudes is the most influential factor. Keywords: COVID-19; Community; Preventive behavior.